Alternative paradigm for language acquisition - Yaacob, Solehah@Nik Najah Fadilah; Abdul Ghani, Rozina; Abu Bakar, Radhwa; Abd. Rahman, Akmal Khuzairy; Ismail, Taufik; Adam, Zalika (Scientific Research, 2014)
In order to have a balanced judgment on language process views, the research tries to explain the mental process connection in the language learning process. The deep structure and surface structure theory designation indicated that the learning process consists of two procedures; deep structure process, which is the essential part in absorbing and captivating activities and surface structure which concentrates on symbols and codes in expressing the mind’s activities. These procedures have been emphasized by modern and traditional scholars in highlighting the concept of the language learning process.